Measurement of radiation dose by a radiologist from Transarterial Chemoembolization (TACE) intervention with optically stimulated luminescence - Kaewmarong, Kanchana; Teebumrung, Nitinard; Awikunprasert, Panatsada; Kittichotwarat, Sirikarn; Claimon, Torpong; Dachviriyakij, Tanapol (Journal of Medicine and Health Sciences, 2023)
The radiation dose received by radiologists during the transarterial chemoembolization (TACE) intervention procedure for the treatment of liver cancer patients and to help prevent future radiation risks for the radiologists. The purpose of this study was to measure the radiation dose at the lens, thyroid, and hand of radiologists during the TACE procedure. The risk and factors affecting radiation dose received by radiologists during TACE procedures were also evaluated. The data were from two radiologists performing TACE procedure with 16 patients. OSL nanoDots dosimeter were attached to outer center of thyroid shield, outside the lead glasses on both sides, and on both wrists of the radiologist to measure the radiation dose during TACE interventional radiology. The results showed that the mean time spent on TACE procedure was 70.8 minutes, the mean of X-ray fluoroscopy time was 19.1 minutes. Without using radiation protective equipment, radiologists received the average radiation doses to thyroid, left eye, right eye, left hand, and right hand were 21.8, 56.1, 6.4, 99.5, and 15.6 µSv, respectively. The maximum TACE cases that can be performed is 29 per month. While using the radiation protection equipment will reduce the doses to thyroid, left eye and right eye to 4.1, 13.1 and 1.2 µSv respectively, and a maximum of 128 procedures could be performed per month. In summary, the radiation dose received by the radiologist during the TACE procedure is within the radiation safety limit. The use of radiation protective equipment is important and necessary to reduce radiation hazards. Radiation workers should avoid radiation exposure when using high radiation doses and techniques.